El ejercicio de la ciudadanía en época de la pandemia COVID–19 en la ciudad de Arequipa - Serruto Castillo, Alison (2021)
The study aims to know the impact of the state of emergency on the exercise of citizen rights during the COVID-19 pandemic in the period from March to November 2020 in the Arequipa region. The research used a mixed methodology, making use of techniques such as documentary review and a virtual survey of Arequipeños citizens over 18 years of age, basic type, descriptive level, non-experimental cross-sectional design. Regarding the sample, a total of 384 people were surveyed. Among the most relevant results, it is shown that the restricted rights that have generated the greatest discomfort in the population are those related to freedom of assembly, freedom of movement and the right to work. And among the unrestricted violated rights are the rights of the child and that of equality between individuals.